Rediscovery and lectotypification of Scutellaria tubiflora (Lamiaceae): an endangered species endemic to Brazil - Alves, David Dos Santos; Carneiro-Torres, Daniela Santos; Antar, Guilherme Medeiros (Phytotaxa, 2025)
We report the rediscovery of Scutellaria tubiflora, a species endemic to Brazil that was previously known only from its type material collected over 190 years ago by the German botanist Friedrich Sellow. Here, we provide a complete description, comparisons with similar species, an updated distribution, a preliminary conservation assessment, a lectotype designation, and illustrations.